2014
DOI: 10.1007/s12010-014-1418-9
|View full text |Cite
|
Sign up to set email alerts
|

Exoelectrogenic Bacterium Phylogenetically Related to Citrobacter freundii, Isolated from Anodic Biofilm of a Microbial Fuel Cell

Abstract: An electrogenic bacterium, named Citrobacter freundii Z7, was isolated from the anodic biofilm of microbial fuel cell (MFC) inoculated with aerobic sewage sludge. Cyclic voltammetry (CV) analysis exhibited that the strain Z7 had relatively high electrochemical activity. When the strain Z7 was inoculated into MFC, the maximum power density can reach 204.5 mW/m(2) using citrate as electron donor. Series of substrates including glucose, glycerol, lactose, sucrose, and rhammose could be utilized to generate power.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…have also been observed in MFC biocathodes and a highly productive methanogenic biocathode supplemented with zero valent iron. ,, Other putative exoelectrogens were also detected at a higher relative abundance in the biogas-fed biocathode than in the CO 2 -fed biocathode. Ochrobactrum and Citrobacter species have previously been isolated from MFC bioanodes and identified as exoelectrogens. , In the present study, Ochrobactrum spp. and Citrobacter spp.…”
Section: Resultsmentioning
confidence: 50%
“…have also been observed in MFC biocathodes and a highly productive methanogenic biocathode supplemented with zero valent iron. ,, Other putative exoelectrogens were also detected at a higher relative abundance in the biogas-fed biocathode than in the CO 2 -fed biocathode. Ochrobactrum and Citrobacter species have previously been isolated from MFC bioanodes and identified as exoelectrogens. , In the present study, Ochrobactrum spp. and Citrobacter spp.…”
Section: Resultsmentioning
confidence: 50%
“…The present study exhibited a maximum power density of 212 mW/m 2 ( Figure 5 ) with a recovery of 13.3% ( Figure 6 ) as an electrical current using the strain KVM11 in acetotrophic conditions. Such findings suggest that the strain KVM11 is also capable of utilizing insoluble electron acceptors with the additional distinctive features making this strain unique from its counterparts ( Xu and Liu, 2011 ; Huang et al, 2015 ; Liu et al, 2016 ), which include, (i) ability to degrade PH, (ii) dye detoxification in MERS, and (iii) anoxic Fe(III) reduction. The typical polarization curve of Citrobacter strain KVM11 ( Figure 7 ) in an acetate-fed MFC indicated a large potential drop due to activational losses as shown in other exoelectrogenic strains ( Park et al, 2001 ; Pham et al, 2003 ; Venkidusamy and Megharaj, 2016a , b ).…”
Section: Resultsmentioning
confidence: 98%
“…With regards to the Citrobacter strains, for example, Citrobacter sp. LAR-1 ( Liu et al, 2016 ) and C. freundii Z7 ( Huang et al, 2015 ) have also shown to be Fe(III) reducing exoelectrogens, although the rate of Fe(III) reduction is unknown. The strain KVM11 displayed a wide nutritional spectrum as highlighted by its utilization of various carbon sources under anaerobic conditions from its counterparts, Citrobacter sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARB can conduct extracellular electron transfer via direct electron transfer (DET) and/or mediated electron transfer (MET) [Kim et al 1999], which is also held by iron-reducing bacteria (FRB), such as Shewanella and Geobacter sp., that can grow upon reduction of Fe(III) [Kostka et al 2002]. Most ARB strains were identified from anodic biofilm of an operating MFC (recent review is available in [Huang et al, 2015]. Conversely, the studies on the use of pure cultures FRB isolated from non-MFC samples as inoculum for startup of an MFC are rare [Liu et al, 2014].…”
Section: Introductionmentioning
confidence: 99%